Retrospective study of single dose of antibiotic in laparoscopic appendicectomy - Kotwal, Shubham Ramanbhai; S. Jadav, Jayeshkumar (International Surgery Journal, 2018)
Background: Laparoscopic appendicectomy for interval appendix is becoming popular among the surgeon. Aim of the study is whether a single dose of antibiotic in laparoscopic appendicectomy is sufficient. Methods: A case study of 30 cases of laparoscopic appendicectomy performed with the use of single dose per-operative antibiotics in Guru Gobind Singh Hospital, Jamnagar in various surgical units from year 2015-2016. Result: Wound infection is present in 10% of the cases, with none of the patients suffering Grade 3 or 4 wound infections. Conclusions: It conclude that a single dose of antibiotic is sufficient for patient undergoing laparoscopic appendicectomy interval appendix.